The effect of paclitaxel (taxol) on the reproductive system and the semen parameters as well as on other organs of male rats. - KOEHLER-SAMOUILIDOU (ΓΚ. ΚΕΛΕΡ-ΣΑΜΟΥΗΛΙΔΟΥ), G.; KALDRYMIDOU (Ε. ΚΑΛΔΡΥΜΙΔΟΥ), E.; PAPAIOANNOU (Ν. ΠΑΠΑΪΩΑΝΝΟΥ), N.; KOTSAKI-KOVATSI (Β-Π. ΚΩΤΣΑΚΗ-ΚΟΒΑΤΣΗ), V. P.; VADARAKIS (Α. ΒΑΝΤΑΡΑΚΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The effect of the administration of paclitaxel on the male reproductive organs as well as on several semen parameters and other organs of Wis tar rats was studied. To 14 weeks old rats 12,4 mg paclitaxel/kg b.w.were administered i.p. once a week for 4 weeks. Six days after the last injection of paclitaxel ten animals, five (n=5) test (group Al) and five control animals (group A2) were sacrificed. Another ten animals, five (n=5) test (group Bl) and five (n=5) control animals (group B2) were sacrificed eleven weeks after the last injection of paclitaxel. The weights of the testes, the epididymis and the prostate gland of the test animals (group Al) were decreased as compared to the control animals (group A2). The number and the motility of the test animal spermatozoa were decreased, and many of them were abnormal. Histologically, the dividing cells and round spermatids were most affected. Leydig cells appeared degenerated. The epithelium of the ductucs epididymis was cuboidal and cell microvilli were absent. There was infiltration of neutrophils. The prostate gland was cystic with degeneration and desquamation of the epithelial cells. In the adrenals cellular degeneration and histiocytic infiltration were observed. In the spleen myeloid metaplasis and in the liver local allergic reaction around the interlobular bile ducts were observed. The weights of the testes, the epididymis and the prostate glands of the test animals (group Bl) were normal as compared with the control animals (group B2). The sperm motility was also normal but the number of spermatozoa was still decreased as compared with the control animals (group B2). Histologically, all examined organs were similar to those of the control animals.